Il processo contro i senatori Basilio e Pretestato e la gestione dei conflitti politico-religiosi a Roma durante il regno degli Ostrogoti (510-511) - Umberto Roberto (Mythos, 2023)
The trial of Basilius and Praetextatus in 510-511, according to Cassiodorus’s Variae and Gregory the Great’s Dialogi, is an event in the period between the end of the fifth century and the first half of the sixth that confirms the survival of pagan practices and beliefs in Rome. Some members of the senatorial aristocracy of Rome are involved in these practices. Indeed, despite the Christianization of the city, the ability to satisfy the desire to understand events, even if through an interpretation linked to ancient pagan knowledge, increases the influence and power of the senatorial families in their competition with other political and religious institutions for control of the Roman population. Basilius’s and Praetextatus’s necromantic practices were probably justified by the aim of gaining prestige in urban society through the knowledge of occult wisdom.